The efficiency of payments for environmental services in tropical conservation - Wunder, Sven (2007)
Payments for environmental services (PES) represent a new, more direct way to promote conservation. They explicitly recognize the need to address difficult trade-offs by bridging the interests of landowners and external actors through compensations. Theoretical assessments praise the advantages of PES over indirect approaches, but in the tropics PES application has remained incipient. Here I aim to demystify PES and clarify its scope for application as a tool for tropical conservation. I focus on the supply side of PES (i.e., how to convert PES funding into effective conservation on the ground), which until now has been widely neglected. I reviewed the PES literature for developing countries and combined these findings with observations from my own field studies in Latin America and Asia. A PES scheme, simply stated, is a voluntary, conditional agreement between at least one “seller” and one “buyer” over a well-defined environmental service—or a land use presumed to produce that service. Major obstacles to effective PES include demand-side limitations and a lack of supply-side know-how regarding implementation. The design of PES programs can be improved by explicitly outlining baselines, calculating conservation opportunity costs, customizing payment modalities, and targeting agents with credible land claims and threats to conservation. Expansion of PES can occur if schemes can demonstrate clear additionality (i.e., incremental conservation effects vis-`a-vis predefined baselines), if PES recipients’ livelihood dynamics are better understood, and if efficiency goals are balanced with considerations of fairness. PES are arguably best suited to scenarios of moderate conservation opportunity costs on marginal lands and in settings with emerging, not-yet realized threats. Actors who represent credible threats to the environment will more likely receive PES than those already living in harmony with nature. A PES scheme can thus benefit both buyers and sellers while improving the resource base, but it is unlikely to fully replace other conservation instrument